Um estudo da ação empreendedora dos lojistas de telefonia móvel pessoal em Londrina - PR - Pessoa, Demeure Adolfo Menezes (2006)
The present work had the main objective to analyze the entrepreneurial action of personal of storeowners of personal telephony franchises in the city of Londrina - Paraná. About to arrive the main objective have been realized research bibliographic and documentary, in addition to collection of data, qualitative nature research. Was analyzed the activity of the personal mobile telephony in Londrina, Paraná - State. It was identified if the chief strategies from the mobile telephony operators in the city. Have been analyzed and discussed the strategies that the franchises storeowners use to maintain their activities, as well the description of the most important characteristics in their operation of the franchised stores was made and the analisys of what the actions entrepreneurial what they assist to keep their business. Have been related the themes of entrepreneurialism, strategy for the literature revision of this work. It was used in this work as a research methodology of multiple cases study with interviews near a small sample of franchise storeowners from four personal mobile telephones companies acting in the marketplace site. The outcomes from collection of data have been analyzed qualitatively and made evident the entrepreneurial actions from the storeowner franchises, what ally strategies from the operator, uses strategies proper to range yours objectives, signal only one positive among the stores of major postage and more innovative owners.